2016
DOI: 10.1002/cplu.201600270
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Theoretical Study of Salts of the [B9H14] Ion: Isolation of Multiple Isomers and Implications for Energy Storage

Abstract: Boranes and boron hydrides are well known for their novel molecular structures and useful chemical reactivity, with [B9H14]− notable in particular for its ease of isolation, unusual structure, and tautomerization. We report an experimental and theoretical investigation of the structure of [B9H14]− and the energetics of some of its reactions. Salts of [B9H14]− with 1‐ethyl‐3‐methylimidazolium and N‐butyl‐N‐methylpyrrolidinium were characterized by single‐crystal X‐ray diffraction and demonstrate the stabilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…A second report gives structures of B 9 H 14 − salts and suggests a new isomer exists in EIL materials. 34 The research described here includes an investigation of the experiments reported by Rogers et al on the decaborane doping of DCA − EILs. This work complements two recent studies from this research group that strive to correlate hypergolicity with the proton transfer properties of the constituent ions in an EIL.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A second report gives structures of B 9 H 14 − salts and suggests a new isomer exists in EIL materials. 34 The research described here includes an investigation of the experiments reported by Rogers et al on the decaborane doping of DCA − EILs. This work complements two recent studies from this research group that strive to correlate hypergolicity with the proton transfer properties of the constituent ions in an EIL.…”
Section: ■ Introductionmentioning
confidence: 99%
“…DFT calculations in the gas phase are quite reliable, and allow for obtaining good structural data and vibrational frequencies, in particular when anharmonicity is included. Several studies report the formation enthalpy of borohydride ions in the gas phase [69][70][71][72] Anharmonic DFT calculations allow for obtaining improved agreement with experimental vibrational spectra, from which heat capacity data were calculated [73]. Figure 2 compares experimental [74] and DFT calculated [69][70][71][72] formation enthalpy data for neutral and anionic boron hydrogen species.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…Several studies report the formation enthalpy of borohydride ions in the gas phase [69][70][71][72] Anharmonic DFT calculations allow for obtaining improved agreement with experimental vibrational spectra, from which heat capacity data were calculated [73]. Figure 2 compares experimental [74] and DFT calculated [69][70][71][72] formation enthalpy data for neutral and anionic boron hydrogen species. Figure 2 shows that the calculated formation enthalpy for a given species (e.g., B 3 H 8 − ) can differ by about 100 kJ/mole for different sources.…”
Section: Dft Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 We previously found that B 10 H 14 reacted spontaneously with ions from energetic azolium ILs to form stable IL-soluble species, 11 such as [B 9 H 14 ] − formed through deprotonation and rearrangement of B 10 H 14 . 12 B 10 H 14 is therefore an interesting main group probe for reactivity with [C 2 mim][OAc] because it possesses Lewis acidic sites of variable nature which may prefer the [OAc] − ion or the carbene.…”
Section: Introductionmentioning
confidence: 99%